Analysis of anteroposterior-to-transverse ratio in predicting thyroid malignancy on ultrasonography. Issue 5 (14th May 2023) - Guo, Q; Li, J; Xin, J; Chen, X
Abstract: Objective: To explore the diagnostic value of anteroposterior-to-transverse ratio for predicting thyroid cancer. Methods: A total of 2306 nodules were divided into 5 groups according to their size. The ability of the anteroposterior-to-transverse ratio to predict thyroid cancer was analysed in each group on the basis of the sensitivity, specificity, accuracy and Youden index. Results: The median anteroposterior-to-transverse ratio was 0.83, with an interquartile range of 0.28. The area under the receiver operating characteristic curve was 0.709 ( p < 0.001). When the diameter of a thyroid nodule was less than 1.5 cm, an anteroposterior-to-transverse ratio of more than 0.9 was associated with higher sensitivity, accuracy and Youden index, compared with an anteroposterior-to-transverse ratio of greater than 1.0, but the specificity was lower. When the diameter of a thyroid nodule was 1.5 cm or more, an anteroposterior-to-transverse ratio of greater than 0.9 was associated with higher sensitivity and Youden index, compared with an anteroposterior-to-transverse ratio of greater than 1.0, but specificity and accuracy were lower. Conclusion: The anteroposterior-to-transverse ratio was a meaningful indicator of thyroid cancer, and its predictive effectiveness could be influenced by nodule size.